Selective glucose electro-oxidation catalyzed by TEMPO on graphite felt - Ginoux, Erwann; Rafaïdeen, Thibault; Cognet, Patrick; Latapie, Laure; Coutanceau, Christophe (Frontiers in Chemistry, 2024)
Long-term electrolyses of glucose in a potassium carbonate (K2CO3) aqueous electrolyte have been performed on graphite felt electrodes with TEMPO as a homogeneous catalyst. The influences of the operating conditions (initial concentrations of glucose, TEMPO, and K2CO3 along with applied anode potential) on the conversion, selectivity toward gluconate/glucarate, and faradaic efficiency were assessed first. Then, optimizations of the conversion, selectivity, and faradaic efficiency were performed using design of experiments based on the L9 (34) Taguchi table, which resulted in 84% selectivity toward gluconate with 71% faradaic efficiency for up to 79% glucose conversion. Side products such as glucaric acid were also obtained when the applied potential exceeded 1.5 V vs. reversible hydrogen electrode.